Recurrent tuberculosis: a systematic review and meta-analysis of the incidence rates and the proportions of relapse and reinfection - Vega, V (Thorax, 2021)
BACKGROUND: A recurrent tuberculosis (TB) episode results from exogenous reinfection or relapse after cure. The use of genotyping allows the distinction between both. METHODS: We did a systematic review and meta-analysis, using a MEDLINE, Lilacs/Scielo, and Cochrane search for studies in English, French, and Spanish published between January 1, 1980 andSeptember 30, 2020 that assessed recurrences after treatment success and/or differentiated relapses from reinfections using genotyping. We calculated person-years of follow- up and performed random-effects model meta-analysis for estimating pooled recurrent TB incidence rates and proportions of relapses and reinfections. We performed subgroup analysis by clinical-epidemiological factors and by methodological study characteristics. FINDINGS: The pooled recurrent TB incidence rate was 2.26 per 100 person-years at risk (95%CI 1.87–2.73; 145 studies). Heterogeneity was high (I(2)=98%). Stratified pooled recurrence rates increased from 1.47 (95%CI 0.87–2.46) to 4.10 (95%CI 2.67–6.28) per 100 person-years for studies conducted in low vs. high TB incidence settings. Background HIV prevalence, treatment drug regimen, sample size and duration of follow-up contributed too. The pooled proportion of relapses was 70% (95%CI 63–77%; I(2)=85%; 48 studies). Heterogeneity was determined by background TB incidence, as demonstrated by pooled proportions of 83% (95%CI 75–89%) vs 59% (95%CI 42–74%) relapse for studies from settings with low vs. high TB incidence, respectively. INTERPRETATION: The risk of recurrent TB is substantial and relapse is consistently the most frequent form of recurrence. Notwithstanding, with increasing background TB incidence the proportion of reinfection increases and the predominance of relapses among recurrences decreases. PROSPERO REGISTRATION NUMBER: CRD42018077867